FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2011-2013 - Wicaksono, Santiko; Nasir, Mohamad (Faculty of Economics and Business Diponegoro University, 2014)
This study aims to determine the effect of profitability, liquidity, leverage, growth and firm size on dividend policy. The population in this study are all companies listed in Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling or sampling based on criteria - criteria, namely: (1) companies that earn profits in a row from 2011-2013. (2) The financial statements of companies using local currency. (3) a company that always pay dividends in a row in 2011-2013. The analytical tool used is multiple linear regression analysis. Based on the results of tests performed can be seen that: (1) Profitability positive effect on dividend policy, meaning that the higher the profitability, the higher the dividend. (2) Liquidity no effect on dividend policy. (3) Leverage has no effect on dividend policy. (4) Growth negatively affect the Company's dividend policy, meaning that the higher the growth of the company, it will reduce the dividend policy (5) Firm size has no effect on dividend policy.